"Guide or conversation?" The experience of Second-Generation Pakistani Muslim men receiving CBT in the UK. Issue 1 (2nd January 2020) - Tarabi, Said Aris; Loulopoulou, Angela Ioanna; Henton, Isabel
Abstract: Islam constitutes the world's second largest religious group. In the United Kingdom (UK), Islam is the second largest religion after Christianity; the largest group of Muslims in the UK is of Pakistani heritage. This qualitative practice-based research study used Interpretative Phenomenological Analysis to explore the experiences of six second-generation Pakistani Muslim men (SGPMM) who had completed cognitive-behavioural therapy (CBT) in the UK. Three superordinate themes were generated: "Pre-CBT difficulties, " "The process of CBT, " and "The interaction between CBT and Islam." This paper elaborates the second theme, "The process of CBT, " as the researchers believe it offers the strongest implications for clinical practice and research. This theme captures participants' thoughts and feelings about the process of their therapy, and further consists of four sub-themes: "Experience of therapeutic dialogue: Guide or conversation?" "Experience of matching: Tailor or taboo?" "Benefits of CBT: Simple tools, big impact, enlightenment", and "Limitations of CBT: Problems with language." These findings seek to inform counselling psychologists and services working with SGPMM, to contribute meaningfully to existing research literature, and to encourage future research.